Access protocols for railroads: Reframing the infrastructure separation debate. (November 2021) - Allen, John G.; Newmark, Gregory L.
Abstract: The Manichean framing of organizational arrangements for railroads as either vertical integration or infrastructure separation does not encompass the full array of access options in the industry. This paper views the conversation about access to rail infrastructure as an institutional matter substantially independent from economic debates regarding rail organization. This research identifies a taxonomy of six access protocols which describe distinct arrangements for the use of railways, considers the conditions conducive to each institutional structure, and illustrates each category with actual examples from across the world. This effort seeks to expand the debate about railroad institutional structures to include the full panoply of existing access arrangements.